2017
DOI: 10.1017/s1368980017001604
|View full text |Cite
|
Sign up to set email alerts
|

The mismatch between observational measures and residents’ perspectives on the retail food environment: a mixed-methods approach in the Heart Healthy Hoods study

Abstract: Objective: To gain a deeper understanding of the retail food environment by investigating similarities and differences between objective measures and residents' perspectives. Design: The study incorporated Geographic Information System (GIS)-based measures, in-store surveys and the results from a larger photovoice project. We combined these data using a convergent parallel mixed-methods approach. Setting: We conducted this study in a low-income neighbourhood in Madrid (Spain) in 2016. Subjects: We assessed hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 45 publications
1
21
0
1
Order By: Relevance
“…Qualitative interview results supported this finding, as participants reported having availability and access to fresh food products in chain grocery stores or farming fields. These findings corroborated results from other studies in rural communities in the US and other international setting that grocery stores offer more healthful food selections but are outnumbered by convenience stores [ 23 – 25 ]. Although convenience stores offer fewer varieties of healthful food choices, [ 16 , 24 27 ] they are also located in more accessible areas, potentially leading to higher customer traffic of neighborhood residents [ 24 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Qualitative interview results supported this finding, as participants reported having availability and access to fresh food products in chain grocery stores or farming fields. These findings corroborated results from other studies in rural communities in the US and other international setting that grocery stores offer more healthful food selections but are outnumbered by convenience stores [ 23 – 25 ]. Although convenience stores offer fewer varieties of healthful food choices, [ 16 , 24 27 ] they are also located in more accessible areas, potentially leading to higher customer traffic of neighborhood residents [ 24 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…Although convenience stores offer fewer varieties of healthful food choices, [ 16 , 24 27 ] they are also located in more accessible areas, potentially leading to higher customer traffic of neighborhood residents [ 24 , 27 , 28 ]. A recent study showed that proximity helps individuals build close social ties with food store owners impacting their preference to shop in smaller food stores [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…These projects took place between 2015–2017 in Villaverde, a low-income District located in the southeastern part of the city of Madrid (Spain). These Photovoice projects aimed to identify both environmental facilitators and barriers to residents’ food choices and physical activity [ 25 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Following Wang’s Photovoice methodology [ 28 ], we divided the Photovoice process into several sessions [ 25 , 35 ]. First, in an initial session, we explained the project aims and scope and discussed the group sessions schedule with participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation